Phytosterol, lipid and phenolic composition, and biological activities of guava seed oil - Adchara Prommaban (2020)
© 2020 by the authors. Plant seeds have been found to contain bioactive compounds that have potential nutraceutical benefits. Guava seeds (Psidium guajava) are by-products in the beverage and juice industry; however, they can be utilized for a variety of commercial purposes. This study was designed to analyze the phytochemicals of the n-hexane extract of guava seed oil (GSO), to study its free-radical scavenging activity, and to monitor the changes in serum lipids and fatty acid profiles in rats that were fed GSO. The GSO was analyzed for phytochemicals using chromatographic methods. It was also tested for free-radical scavenging activity in hepatoma and neuroblastoma cells, and analyzed in terms of serum lipids and fatty acids. GSO was found to contain phenolic compounds (e.g., chlorogenic acid and its derivatives) and phytosterols (e.g., stimasterol, β-sitosterol and campesterol), and exerted radical-scavenging activity in cell cultures in a concentration-dependent manner. Long-term consumption of GSO did not increase cholesterol and triglyceride levels in rat serum, but it tended to decrease serum fatty acid levels in a concentration-dependent manner. This is the first study to report on the lipid, phytosterol and phenolic compositions, antioxidant activity, and the hepato- and neuro-protection of hydrogen peroxide-induced oxidative stress levels in the GSO extract.